Intellectual production and scientific visibility - Turpo, Josué E. (2013)
One of the dimensions required by accrediting agencies to universities is that no production of knowledge. The latest 2013 SIR (SCImago group) shows that Latin American universities are confined in research compared to U.S. or European universities at the same time notes that research in Peru is poor, and more so in the universities confessional. Based on the premise that “the science is not there " and that new intellectual production normativities which warrant is necessary to analyze the scientific production and its relation to visibility. This study recounts the experience of the Journal of College and Research Notes how it has become the second international refereed journal Peruvian Union University, at the same time explains the steps taken to be included in the catalogs of magazines important in Latin America.